﻿ Principle of transformation of mechanical energy to electric

# As mechanical energy will be transformed to electric

The conductor of AB (Fig. 1) moves with constant speed due to mechanical energy of any prime mover — the source of mechanical energy.

Principle of transformation of energy.

Mechanical power of the movement of the conductor

RMEH = Fv,

where F — force operating on the conductor from the prime mover.

Thanks to electromagnetic induction in the conductor works э. of page is also current

I = E: (r0 + r),

where r0 — resistance of the conductor of AB (internal resistance of the source of electrical energy); r — resistance of the external part of the chain, including resistance of the receiver and the part of tires entering the contour

Fig. 1 Movement of the lead conductor in magnetic field.

The conductor of AB is in this case the source э. of page, which electric power

P = EI

Size P is often called electromagnetic power. With the advent of current in the conductor of AB there is electromagnetic force of FM operating in the direction, perpendicular to the direction of current. Applying the left-hand rule, it is possible to be convinced that the electromagnetic force of FM is directed against F force.

Therefore, the external force of F is in this case driving, and FM — brake.

With the constant speed of v (the established movement) driving and brake forces are equal:

F = FM = BIl (B - magnetic induction)

Substituting expression of force in the formula (RMEH = to Fv), we will receive:

RMEH = Fv = BIlv

As

Bvl = E,

that

RMEH = Fv = P

Therefore, the mechanical power of the prime mover is equal to the electric power of the source. Expression (RMEH = Fv = P) shows that at the movement of the conductor in magnetic field in the direction of mechanical force there is the full transformation of mechanical energy to electric. Tension on the ends of the conductor of UAB is at the same time tension on the external part of the chain. This tension is less э. of page at the size of internal falling the napryazhniya

UAB = E – Ir0 = Ir